Adobe InDesign CS2 Revealed - Botello, Chris (Course Technology, 2005)
Geared towards beginner-to-intermediate level InDesign users, "Adobe InDesign CS2 Revealed" offers a complete look at AdobeÂ's latest release of its popular layout software, InDesign. Following a unique style that caters towards beginners, "Adobe InDesign CS2 Revealed" provides step-by-step tutorials to teach the skills needed to master the InDesign software. Featuring a user-friendly design and easy-to-follow instructions, the book provides detailed coverage of the software through design projects such as creating advertisements, brochures, and flyers, putting concepts and skills into a real-world context